2008
DOI: 10.1002/jmv.21213
|View full text |Cite
|
Sign up to set email alerts
|

Seoul virus enhances regulatory and reduces proinflammatory responses in male Norway rats

Abstract: Zoonotic pathogens, including hantaviruses, are maintained in the environment by causing persistent infection in the absence of disease in their reservoir hosts. Spillover of hantaviruses to humans can cause severe disease that is mediated by excessive proinflammatory responses. The mechanisms mediating hantaviral persistence in rodent reservoirs remain largely unknown. Male Norway rats were inoculated with their species-specific hantavirus, Seoul virus (SEOV), and viral RNA, cytokine, and chemokine responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 49 publications
3
91
1
Order By: Relevance
“…We thus examined whether we could detect an effect of Tnf-a and Mx2 constitutive gene expression (these genes do not seem to be upregulated in rodent spleen following hantavirus infection; Easterbrook and Klein, 2008;Schountz et al, 2012;Spengler et al, 2013) on PUUV replication in wild bank voles. We considered the data set including infected bank voles only (N ¼ 33).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We thus examined whether we could detect an effect of Tnf-a and Mx2 constitutive gene expression (these genes do not seem to be upregulated in rodent spleen following hantavirus infection; Easterbrook and Klein, 2008;Schountz et al, 2012;Spengler et al, 2013) on PUUV replication in wild bank voles. We considered the data set including infected bank voles only (N ¼ 33).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to extract RNA from the spleen because this organ has important immune functions (it is a secondary lymphoid organ) and is the site of low levels of PUUV replication (Korva et al, 2009). Moreover, experimental studies that have followed the kinetics of immune gene expression in rodent hosts infected by hantaviruses all showed that the expression of Tnf-a gene remained unchanged in the spleen of infected rodents from the time of infection to 40 days post-infection or compared with uninfected ones (Easterbrook and Klein, 2008;Schountz et al, 2012;Spengler et al, 2013). Spleens therefore reflect the constitutive levels of Tnf-a and Mx2 expression, not influenced by PUUV infection but potentially modulated by other infections that should mainly be randomly distributed between PUUV-infected and PUUV-non-infected voles.…”
Section: Quantification Of Tnf-a and Mx2 Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some chemokines are elevated in the spleens of infected rats, including Ccl2 and Ccl5, but less so in the lungs (9).…”
mentioning
confidence: 96%